Characteristics and Properties of Stream Runoff from Watersheds in Northeast Thailand - Wirojanakud, Prakob; Srivoramas, Rerkchai (Engineering and Applied Science Research, 2013)
Lacks of geographic and hydrological data system of watershed has been a limit to hydrological analysis for water resource development. Existing data are scattering among government offices and are yet to be analyzed. This research is to solve this problem by collecting and collating hydrological and watersed data and derive runoff characteristics for middle and large scale basins (basins of order 5, 6, 7 and 8) in northeast of Thailand. From this study, in the zone of annual rainfall less than or equal 1,300 mm, the streams of order 5 and 6 have most of the runoff in rainy season and the maximum runoff are in September at about 30 percent of annual runoff. The average monthly runoff in dry season is about 2% of the annual runoff. For the stream of order 7 and 8, maximum runoff is in September to October. The maximum runoff that occurs in October is usually higher than in September. In zone of annual rainfall greater than 1,300 mm, the runoff from basin of order 5, 6, 7 and 8 are mainly in rainy season. The maximum runoff occurs in September and October. The average monthly runoff in dry season is about 3% of the annual runoff in the dry season than others. The order 5 and 6 basin have very little runoff when compare to the order 7 and 8 basin. Regression analysis of runoff and other characteristics of the medium-size watersheds reveal that annual runoff fits well with the watershed area and main river length but not conform to slope of the basin and annual rainfall because of a little variation of annual rainfall in Northeast Thailand. However, since the rain is a source of runoff, rainfall was considered in runoff analysis using the concept of runoff coefficient which was investigated in this study. Besides, runoff from groundwater does not relate to basin characteristics. Prediction of maximum runoff in data less basin can be determined from the ratio of maximum flood and average annual flood, which was also investigated in this study.